1994
DOI: 10.1152/ajprenal.1994.266.2.f325
|View full text |Cite
|
Sign up to set email alerts
|

Ionic currents and endothelin signaling in smooth muscle cells from rat renal resistance arteries

Abstract: The repertoire of ionic channels expressed in myocytes freshly isolated from microdissected interlobar and arcuate arteries of rat kidney and their integrative behavior in response to endothelin-1 (ET-1) were studied by identification and characterization of major whole cell current components using patch-clamp technique. In renal microvascular smooth muscle cells (RMSMC) dialyzed with K(+)-containing solution, rapidly inactivating (Ito) and sustained outward K+ currents were identified. Voltage-dependent Ito … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(106 citation statements)
references
References 0 publications
7
97
2
Order By: Relevance
“…Collectively, our findings suggest that in afferent arterioles, phospholipase C-dependent calcium release from endoplasmic reticulum (35) triggers subsequent cellular responses that activate voltage-dependent calcium channels. Electrophysiological studies indicate the presence of calcium-activated chloride channels on preglomerular vessels, including afferent arterioles (10,36). Furthermore, previous data demonstrated that chloride channel blockade inhibited AngII-induced afferent arteriolar constriction (11,37).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, our findings suggest that in afferent arterioles, phospholipase C-dependent calcium release from endoplasmic reticulum (35) triggers subsequent cellular responses that activate voltage-dependent calcium channels. Electrophysiological studies indicate the presence of calcium-activated chloride channels on preglomerular vessels, including afferent arterioles (10,36). Furthermore, previous data demonstrated that chloride channel blockade inhibited AngII-induced afferent arteriolar constriction (11,37).…”
Section: Discussionmentioning
confidence: 99%
“…Second messengers responsible for the ET-1-mediated vascular response include phospholipase C activation and subsequent calcium mobilization from intracellular stores, as well as phospholipase A 2 stimulation, resulting in production of arachidonic acid metabolites. 1,14,21,25 In freshly isolated smooth muscle cells from large-caliber renal vessels, Gordienko et al 25 demonstrated that ET-1-induced mobilization of intracellular calcium was accompanied by membrane depolarization. ET-1 also stimulated Ca 2ϩ -activated K ϩ channels in renal vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…In guinea pig smooth muscle myocytes, endothelin stimulated the activity of a 12-pS channel, that may or may not be carried through T-type channels (181). Endothelin has been reported to have no effect on T-type currents recorded from smooth muscle cells from rat renal resistance arteries (143).…”
Section: B Hormonal Stimulationmentioning
confidence: 97%
“…T-type currents have only been recorded from smooth muscle cells (SMC) isolated from rat interlobular and arcuate arteries (143). Heterogeneity in Ca 2ϩ currents was observed, with approximately one-third of the freshly isolated myocytes displaying only T-type currents ("T-rich"), one-third only L type, and the rest a mixture.…”
Section: Kidneymentioning
confidence: 99%